The role of lipid peroxidation products and antioxidant enzymes in the pathogenesis of aseptic and purulent inflammation in cats - Rudenko, Pavel; Vatnikov, Yuriy; Engashev, Sergey; Kvochko, Andrey; Notina, Elena; Bykova, Irina; Kulikov, Evgeny; Rudenko, Andrey; Petrukhina, Olesia; Rudenko, Viktoriya (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: The work aimed to determine the state of lipid peroxidation products and the activity of the antioxidant system in cats with aseptic inflammation and purulent-inflammatory processes of varying severity. Materials and Methods: The intensity of the process of lipid peroxidation- antioxidant system processes in blood plasma was evaluated using commercial kits. The level of diene conjugates (DC), the content of malondialdehyde (MDA), the level of medium-weight molecules were determined from lipid peroxidation indices. The state of antioxidant protection was assessed by indicators of superoxide dismutase (SOD) activity, catalase (CT), ceruloplasmin (CP) concentration, glutathione peroxidase activity, glutathione reductase (GLR), and total antioxidant activity (AOA). Results: With aseptic inflammation in the blood of cats, a slow activation of peroxidation reactions occurred. The DC indicator increased by 1.4 times, the SOD level rose by 1.38 times, the amount of GLR by 1.04 times, and the activation of total AOA by 9.06. In sepsis, the values of DC, MDA, and medium-weight molecules increased by 4.4, 8.4, and 8.8 times, respectively. With abscesses in the blood of cats, an increase in CT, CP, and GLR is observed against a background of a decrease in glutathione peroxidase. With purulent wounds, the total AOA of plasma increases by 2.5 times; with abscesses, the total AOA increases by 1.9 times, and with sepsis, it decreases by 1.5 times. Conclusion: With surgical infections in cats, deep biochemical changes or irreversible biochemical changes (in sepsis) occur that indicate a significantly enhanced catabolic orientation of metabolic processes and the accumulation of toxic metabolites, which leads to damage and a decrease in tissue regenerative capacity. J. Adv. Vet. Anim. Res., 8(2): 210-217, June 2021